Assembly-Line Balancing by Linear Programming - Bowman, E. H. (Operations Research, 1960)
Linear-programming solutions to the assembly-line balancing problem are offered in two forms. Feasible solutions depend on work recently presented on integer solutions to linear-programming problems. As yet, the computation involved for a practical problem would be quite large.